ANALYSIS CHARACTERISTICS WORK AND THE IMPACT OF NON-PHYSICAL WORK ENVIRONMENT ON PERFORMANCE AT PT. ALVA KARYA PERKASA MEDAN - Hariyansyah, Ferdian Putra; Ferine, Kiki Farida; Nasution, Fitra Arlina (RADJA PUBLIKA, 2025)
This research was conducted at PT. Alva Karya Perkasa Medan with the aim of the research to determine the influence of job characteristics and non-physical work environment partially and simultaneously on employee performance in carrying out their duties. The population is all employees working in the company as many as 120 people and sampling using the Slovin formula so that the number of research samples used is 55 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study show that job characteristics and non-physical work environment partially and simultaneously have a positive and significant effect on employee performance. There is a sufficient correlation between job characteristics and non-physical work environment with employee performance and the percentage is 16.3% and the remaining 83.7% can be explained by other variables not studied.